Influenza-A mediated pre-existing immunity levels to SARS-CoV-2 could predict early COVID-19 outbreak dynamics - Almazán Nerea Martín; Rahbar Afsar; Carlsson Marcus; Hoffman Tove; Kolstad Linda; Rönnberg Bengt; Pantalone Mattia Russel; Fuchs Ilona Lewensohn; Nauclér Anna; Ohlin Mats; Sacharczuk Mariusz; Religa Piotr; et al. (Elsevier Inc., 2025)
Susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections is highly variable and could be mediated by a cross-protective pre-immunity. We identified 14 cross-reactive peptides between SARS-CoV-2 and influenza A H1N1, H3N2, and human herpesvirus (HHV)-6A/B with potential relevance. The H1N1 peptide NGVEGF was identical to a peptide in the most critical receptor binding motif in SARS-CoV-2 spike protein that interacts with the angiotensin converting enzyme 2 receptor. About 62%–73% of COVID-19-negative blood donors in Stockholm had antibodies to this peptide in the early pre-vaccination phase of the pandemic. Seasonal flu vaccination enhanced neutralizing capacity to SARS-CoV-2 and T cell immunity to this peptide. Mathematical modeling taking the estimated pre-immunity levels to flu into account could fully predict pre-Omicron SARS-CoV-2 outbreaks in Stockholm and India. This cross-immunity provides mechanistic explanations to the epidemiological observation that influenza vaccination protected people against early SARS-CoV-2 infections and implies that flu-mediated cross-protective immunity significantly dampened the first SARS-CoV-2 outbreaks.